2020
DOI: 10.1177/1559325820946194
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Rapamycin Pretreatment Alleviates Cerebral Ischemia/Reperfusion Injury in Dose-Response Manner Through Inhibition of the Autophagy and NFκB Pathways in Rats

Abstract: Although rapamycin can attenuate cerebral ischemia/reperfusion (I/R) injury, the potential roles of rapamycin on cerebral I/R injury remain largely controversial. The present work aims to evaluate underlying molecular mechanisms of rapamycin pretreatment on I/R injury. In total, 34 Sprague-Dawley rats were randomly grouped to 3 groups: sham group (n = 2), vehicle group (n = 16), and rapamycin-pretreatment group (n = 16). Before the focal cerebral ischemia was induced, those rats in the pretreatment group were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Erlich et al [8] showed that rapamycin, which induces neuronal autophagy by inhibiting its' mammalian target protein, improved neurological prognosis after TBI. On the other hand, accumulating evidence suggests that the activation of the neuronal autophagy pathway is related to the pathological mechanism of post-traumatic brain injury, and inhibition of this pathway can alleviate brain injury and functional defects [10,15,21]. In our current study, treatment with resveratrol suppressed the expression levels of LC3 II and Beclin-1, and increased P62 in the hippocampus at 12, 24, and 48 hours after injury.…”
Section: Discussionsupporting
confidence: 46%
“…Erlich et al [8] showed that rapamycin, which induces neuronal autophagy by inhibiting its' mammalian target protein, improved neurological prognosis after TBI. On the other hand, accumulating evidence suggests that the activation of the neuronal autophagy pathway is related to the pathological mechanism of post-traumatic brain injury, and inhibition of this pathway can alleviate brain injury and functional defects [10,15,21]. In our current study, treatment with resveratrol suppressed the expression levels of LC3 II and Beclin-1, and increased P62 in the hippocampus at 12, 24, and 48 hours after injury.…”
Section: Discussionsupporting
confidence: 46%
“…Basal autophagic activity exists in cells under physiological conditions, while the process turns more active induced by various stress events including CIRI and plays complex roles ( Wirawan et al, 2012 ). Some studies demonstrated that the activation of autophagy ameliorated CIRI ( Sun et al, 2020b ; Xu et al, 2020 ; Zhang B. et al, 2020 ; Chen et al, 2021 ; Jin et al, 2021 ; Yihao et al, 2021 ; Zha et al, 2021 ), while more research supported that the inhibition of autophagy activation exerted a neuroprotective effect in brain stroke ( Sun et al, 2020a ; Zhang et al, 2020b ; Li and Huang, 2020 ; Mei et al, 2020 ; Shi et al, 2020 ; Wang L. et al, 2020 ; Gu et al, 2021 ; Liu N. et al, 2021 ; Shao et al, 2021 ; Wang C. et al, 2021 ; Xu et al, 2021 ; Yao et al, 2021 ; Zhang et al, 2021 ; Zhao et al, 2021 ). Obviously, the controversial dual role of the induction of autophagy in the ischemic brain is still a hot topic in research and remains to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In an early study, rapamycin has been confirmed to promote tumor cell apoptosis by promoting autophagy. [32][33][34] However, several studies reported that rapamycin can reduce ischemia-reperfusion injury, [35][36][37] delay cell senescence, and prolong the lifespan. [38][39][40] As reported by a recent study, ADSCs pretreated by rapamycin can further promote the angiogenesis and survival of fat grafts.…”
Section: Discussionmentioning
confidence: 99%